(untitled) (Bioagro, 2020)
Pineapple (Ananas comosus (L) Merrill) is one of an economically cultured crops in Taiwan. It is normally cultivated in soils containing strong acidity where aluminum (Al) often inhibits the growth of crop roots. This research was carried out with the objective of identifying the main genes that directly influence aluminum tolerance by resistant and non-resistant pineapples (Cayenne and Tainung No. 17, respectively). For this reason, both cultivars were grown in hydroponic nutrient solution, each containing 0 and 300 μM AlCl3, in a growth chamber for four weeks. Samples of root apices were taken, followed by extraction of RNA, selection of primers, sequencing and processing of PCR. Finally, after examination of genes, the relative expressions of them for both cultivars were determined by quantitative PCR. The results obtained from polymerase chain reaction experiments proved the Al-resistance characteristics of pineapples are mainly regulated by two genes, namely GAPDH (glyceraldehyde-3-phosphate-dehydrogenase) and FBA (fructose biphosphate adenosine). This result may provide important indications for the study of advancing genetic mechanisms on Al-resistance in pineapples.